Quantifying quality of learning during teaching an undergraduate unit: Manufacturing processes - Pramanik, Alokesh; Islam, Mohammad Nazrul (Springer, 2015)
Multiple choice questions have been introduced in the Manufacturing Processes 233 unit at Curtin University recently to assess students’ learning in this core subject. The questions were set based on the learning outcomes proposed in the unit outline. There are three learning outcomes of this unit. This paper investigates students’ learning capability and approach of answering questions based on the learning outcomes. The analysis was performed by interpreting the students’ answers in the midterm and final examinations. It was found that students’ overall learning in this unit was reasonably good. However, students performed better in the area where knowledge can be applied directly to the workplace. On the other hand, students are marginally weaker in understanding theoretical and analytical facts of the subject matter.